Methodology for Assessing Damage to Forest Ecosystems as a Result of the Creation of Trenches - Didukh, Ya. P.; Hrad, Yu. A.; Moysiyenko, I. I. (Ukrainian Geographical Journal, 2025)
The article presents a methodology for assessing the damage caused by the creation of military trenches. It calculates the regulating and supporting ecosystem services based on biomass, mortar and soil energy. The methodology was tested on a 70-year-old pine forest and a 120-year-old oak forest. It provides for the assessment of direct losses caused by military trenches as a result of destruction and indirect losses as a result of damage to different ecosystem components, taking into account the time needed for recovery to the native state. The monetary value of the losses due to trenches of 42 m2 for pine and oak forests is 49.5 and 56.6 thousand USD, respectively, and the indirect losses due to dumps of 166.7 m2 are 61.9 and 70.8 thousand USD, respectively. The methodology can be used for the purpose of compensation of the damage caused to the natural ecosystems.